Applications of metal–organic frameworks for oral delivery systems - Wenjuan Jiao; Chengdeng Chi (Nano Select, 2022)
Abstract Metal–organic frameworks (MOFs) have been developed to be intelligent delivery systems recently. However, MOFs as oral systems have been challenging. The purpose of this perspective is to briefly review the current applications of oral MOFs and the present dilemma of oral MOFs for humans. The destiny of MOFs‐based materials within the gastrointestinal tract and the blood are discussed, and the principles that guide the development of oral MOFs‐based materials are summarized. It is expected that this perspective will provide new insights on the design and development of oral MOF‐based materials as smart carriers for keeping human health.